Effect of Moringa Leaves Powder Incorporated into Chocolate on the Quality and Stability Properties - Mansoor Abdul Hamid; Jason Siew Kin Ming; Mayrana Md. Nor; Hasmadi Mamat; Jahurul Haque Akanda (Bulletin of Culinary Art and Hospitality, 2021)
This study was carried out to determine the effect of the addition of Moringa oleifera (Moringa) leaves powder? on the antioxidant and sensory properties of chocolate. Three formulations with different percentage of Moringa leaves powder (1, 3, and 5 percent) were studied. Through the hedonic sensory test, there is no significant difference (p less than 0.05) between the formulations for all attributes except the taste. Chocolate with 5 percent Moringa leaves showed the highest total phenolic content and antioxidant activity compared to the other formulations. The addition of moringa leaves caused decreased the chocolate hardness while increased the chocolate average particle size. After 8 weeks of storage, no bloom formation was observed on the surface of the chocolate but the hardness found to be decreased. chocolate associated with moringa leaves powder has potential with health benefit and still has good quality chocolate character.